The taxonomic history of family Plumbaginaceae Juss. of the Ukrainian flora (CHORNOMORSKI BOTANICAL JOURNAL, 2017)
The taxonomic history of the family Plumbaginaceae A.L. Jussieu (1789) of the flora of Ukraine is discribed. Previously, all species of the family Plumbaginaceae in Ukraine were included in a single complex of the genus Statice L. In 1754, F. Miller identified the genus Limonium as an independent. First detailed taxonomic treatment of the genus Limonium was achieved by P.E. Boissier (1848) in his synopsis «Prodromus systematis naturalis regni vegetabilis». I.A. Linchevsky defined the family Limoniaceae Lincz. from Plumbaginaceae as an independent that includes only three genera: Armeria, Goniolimon and Limonium.
Keywords: Limonium, Armeria, Goniolimon.